2022
DOI: 10.1016/j.gore.2022.100930
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of adjuvant treatment and survival outcomes in stage I uterine carcinosarcoma

Abstract: Highlights 5-year survival for stage I uterine carcinosarcoma without adjuvant therapy is 43%. Nationally 40% of stage I uterine carcinosarcoma do not receive adjuvant therapy. Adjuvant chemotherapy alone improved OS and CSS in stage I uterine carcinosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The variability in the reported treatment regimens and outcomes in the literature demonstrates a lack of consensus for carcinosarcoma patients. Early-stage studies indicate that the 5-year survival for stage I uterine carcinosarcoma may be as low as 43% without adjuvant therapy [5]; however, other studies have reported that patients may perform well with only surveillance [2]. Balancing sufficient treatment with an avoidance of potential toxicities is therefore extremely challenging, and recurrences are generally fatal [3].…”
Section: Introductionmentioning
confidence: 99%
“…The variability in the reported treatment regimens and outcomes in the literature demonstrates a lack of consensus for carcinosarcoma patients. Early-stage studies indicate that the 5-year survival for stage I uterine carcinosarcoma may be as low as 43% without adjuvant therapy [5]; however, other studies have reported that patients may perform well with only surveillance [2]. Balancing sufficient treatment with an avoidance of potential toxicities is therefore extremely challenging, and recurrences are generally fatal [3].…”
Section: Introductionmentioning
confidence: 99%